A Case Study On Mergers And Amalgamations Of Canara Bank And Syndicate Bank - Vaishnav Goud Shambula; Mohd. Mansoor Hussain (Involvement International Journal of Business, 2024)
A well-functioning financial system is crucial for a modern economy, with banks playing a vital role in economic and social stability. Public Sector Banks, particularly, are key in generating revenues from rural areas and expanding financial services to underserved regions. This study examines Canara Bank's performance and growth over the past five years, focusing on key financial parameters and the recent merger with Syndicate Bank. The research employs a doctrinal methodology, using secondary data sources, mainly the annual reports of Canara Bank. Key performance indicators analyzed include operating profit, net profit/net loss, net NPA ratio, capital adequacy ratio, and advances, providing a comprehensive overview of the bank's financial health and growth. The analysis reveals trends in Canara Bank's financial performance, with fluctuations in operating profit and net profit, variations in the net NPA ratio, and changes in the capital adequacy ratio. The merger with Syndicate Bank is assessed, highlighting its effects on financial stability and operational efficiency. The merger between Canara Bank and Syndicate Bank is a significant event in the Indian banking sector, with implications for financial inclusion and service expansion in rural areas. The study discusses these impacts, offering insights into how the merger has influenced Canara Bank's performance and strategic direction. The study summarizes key findings and suggests future strategies to enhance Canara Bank's performance post-merger. Recommendations focus on improving financial metrics and leveraging the merger to expand services and increase revenue generation, particularly in rural areas.